Heat balance of billets during hot extrusion of nickel alloy pipes - Medvediev , M. I.; Bobukh , O. S.; Kuzmina , O. M.; Krasiuk , A. V.; Ivanova , L.Kh. (Theory and Practice of Metallurgy, 2026)
Annotation. Among the problems encountered in the production of nickel-based alloy pipes by hot extrusion sleeves on horizontal hydraulic presses, one of the main ones is the high level of product surface defects. To reduce rejects on this basis, it is important to understand the changes in the temperature field of the pipe billet throughout the entire technological process, since this factor is the key to the formation of surface defects in such pipes. The purpose of the work is to establish the regularities of temperature changes in nickel alloy pipe billets at the main stages of pipe production, which are made by extrusion on presses with a force of 16.0 MN and 31.5 MN with the use of glass lubricants. Methodology. The work was performed based on the results of a systematic analysis of the main technological stages of the actual process of producing hot-extruded pipes made of nickel alloy 602CA on presses with a force of 16.0 MN and 31.5 MN. The selected production stages include: transporting the billet (liner) from the induction heater to the glass-filled table, applying glass-filled material to the billet surface, transporting the billet with glass-filled material to the press, holding the billet in a container before extrusion, and extrusion in the container. The calculation of the stepwise temperature loss by the billet was performed using known and own empirical equations obtained from the results of thermography of the billets. The chemical composition of the billets was determined using an Elvax plus spectrometer. The temperature of the outer surface of the workpiece was measured using chromium-aluminium thermocouples complete with an electronic potentiometer. Results. It was found that the total change in the temperature of the sleeves during the cooling process during auxiliary operations on presses with a force of 16.0 MN and 31.5 MN at the same initial heating temperature of the workpieces is inversely proportional to their wall thickness. At the same time, this dependence is almost linear in the range of 40...120 mm wall thickness of the sleeves and 1050...1250 °C heating temperatures of the workpiece. Scientific novelty. For the first time, a methodology for calculating the temperature of the sleeves at the main stages of their preparation for the extrusion process has been developed. Practical utility. The use of the developed methodology for calculating the temperature of the liner allows for a reasonable choice of glass lubricant for the initial technological operations of extrusion on presses with a force of 16.0 MN and 31.5 MN using glass lubricant, which in turn contributes to improving the surface quality of pressed pipes, reducing the level of pipe rejects and reducing the volume of their the volume of their further mechanical processing.